Identifying targets for antibiotic stewardship interventions in pediatric patients in Punjab, Pakistan: point prevalence surveys using AWaRe guidance - Sheikh, Samia; Saleem, Zikria; Afzal, Shairyar; Qamar, Muhammad Usman; Raza, Ali Abuzar; Haider Naqvi, Syed Zeeshan; Al-Rawi, Mahmood Basil A.; Godman, Brian (Frontiers in Pediatrics, 2025)
IntroductionSurveillance of antibiotic use is crucial for identifying targets for antibiotic stewardship programs (ASPs), particularly in pediatric populations within countries like Pakistan, where antimicrobial resistance (AMR) is escalating. This point prevalence survey (PPS) seeks to assess the patterns of antibiotic use in pediatric patients across Punjab, Pakistan, employing the WHO AWaRe classification to pinpoint targets for intervention and encourage rational antibiotic usage.MethodsA PPS was conducted across 23 pediatric wards of 14 hospitals in the Punjab Province of Pakistan using the standardized Global-PPS methodology developed by the University of Antwerp. The study included all pediatric inpatients receiving antibiotics at the time of the survey, categorizing antibiotic prescriptions according to the WHO Anatomical Therapeutic Chemical classification and the AWaRe classification system.ResultsOut of 498 pediatric patients, 409 were receiving antibiotics, representing an antibiotic use prevalence of 82.1%. A substantial majority (72.1%) of the prescribed antibiotics fell under the WHO's Watch category, with 25.7% in the Access category and 2.2% in the Reserve group. The predominant diagnoses were respiratory infections, notably pneumonia (32.4%). The most commonly used antibiotics were ceftriaxone (37.2%) and Vancomycin (13.5%). Only 2% of antibiotic uses were supported by culture sensitivity reports, highlighting a reliance on empirical therapy.ConclusionThe high prevalence of antibiotic use, particularly from the Watch category, and low adherence to culture-based prescriptions underscore the critical need for robust antibiotic stewardship programs in Pakistan. Strengthening these programs could help mitigate AMR and optimize antibiotic use, aligning with global health objectives.